Export promotion programmes and the export performance of Ghanaian firms: The mediating role of foreign market attractiveness. Issue 4 (9th July 2018) - Sharma, Revti Raman; Sraha, Gloria; Crick, Dave
Abstract : Purpose: The purpose of this paper is to examine the mediating role of foreign market attractiveness on the association between export promotion programmes (EPPs) and export performance in the context of Ghanaian firms. In addition to understanding how EPPs help enhance the attractiveness of the foreign markets and thus export performance, the study contributes to the under-developed export performance literature regarding Sub-Saharan African (SSA) firms. Design/methodology/approach: A mixed method approach is utilised. In the first instance quantitative analysis is undertaken on 116 Ghanaian firms via data collected using the drop and pick method. Qualitative data involving interviews with 18 managers of exporting firms are then reported upon. Findings: The study finds full mediation effects for foreign market attractiveness. This suggests that EPPs can enhance export performance via the intervening variable of foreign market attractiveness. Specifically, EPPs should be considered as a resource in managers' ability to develop capabilities in exporting, but need to be considered in the context of other intervening factors such as perceived foreign market attractiveness. Originality/value: The literature regarding EPPs and export performance mostly overlook any link between EPPs and other determinants of export performance towards establishing an indirect relationship between the constructs. The study fills this important gap; in particular, in respect of SSA firms and specifically in the context of Ghana.